Analisis Risiko Kecelakaan dan Bahaya Kerja dengan Metode HIRARC (Hazard Identification Risk Assesment and Risk Control) Bagian Produksi - dedy kunhadi; Giga Prayogi; I Gusti Ayu Sri Deviyanti (Institut Teknologi Adhi Tama Surabaya, 2022)
Even though good regulations and work procedures have been made, the Zero Lost Time Injury program and the provision of personal protective equipment (PPE), work risks and accidents still occur in the production division of PT. XYZ. The purpose of this research is to identify the dangers arising from work accidents and to know the risks of work accidents and the hazards and their impacts. HIRARC (Hazard Identification Risk Assessment and Risk Control) method. by identifying risks, how to assess risk control risk. Data collection is carried out by field observations, interviews, and analysis of standard operating procedure documents. Accident risks and dangers are found in many activities in transportation and unloading of materials, activities for determining finish good into drums, unloading filter paper activities, there are many risks of accidents and hazards including: material fall, being hit by raw material, pinched feet when unloading etc. The impacts include: Minor Injury, P.A.K, Permanent Disability, Major Material Losses, and even Fatality. Strict action against workers who violate regulations and do not use PPE according to standards.